A broad and potent IgM antibody against tetra-EV-As induced by EVA71 and CVA16 co-immunization. Issue 44 (22nd October 2021) - Zhu, Wenbing; Liu, Zhuohang; Zheng, Xuelin; Li, Jun; Lu, Kongjie; Jiang, Xi; Zhang, Xuejian; Ren, Fangfang; Zhang, Xuemei; Xu, Jingwen; Wu, Zhongxiang; Sun, Ming; et al.
Highlights: Generating neutralizing mAbs against EV-As by co-immunization with EVA71 and CVA16. An IgM antibody M20 shows potent and broad neutralizing ability against tetra-EV-A. M20 binds to the GH loop of VP1, may be a candidate for universal vaccines design. Abstract: Objective: To determine the potent and broad neutralizing monoclonal antibody (mAb) against enterovirus A (EV-A) in vitro and in vivo induced by enterovirus A71(EVA71) and coxsackievirus 16 (CVA16) co-immunization. Methods: The mAb was Generated by co-immunization with EVA71 and CVA16 through hybridomas technology. The characteristics and neutralizing ability of mAb were analysed in vitro and in mice. Results: We screened three mAb, the IgM antibody M20 and IgG antibody B1 and C31. All three antibodies showed cross-reactivity against tetra-EV-As. However, M20 showed potent and broad neutralizing ability against tetra-EV-As than B1 and C31. Meanwhile, M20 provided cross-antiviral efficacy in tetra-EV-As orally infected mice. Moreover, M20 binds to a conserved neutralizing epitope within the GH loop of tetra-EV-As VP1. Conclusions: M20 and its property exhibited potent and broad antiviral activity against tetra-EV-As, and that is expected to be a potential preventive and therapeutic candidate against EV-As.